Persistent infection with Strongyloides venezuelensis in the Mongolian gerbil (Meriones unguiculatus) - Baek, Byeong-Kirl (The Korean Society for Parasitology, 2002)
To examine the fate of Strongyloides venezuelensis, Mongolian gerbils (Meriones unguicalatus) were orally infected with 1,000 L(3) larvae per animal. Altogether, 50 gerbils divided into 5 groups of 10 each were monitored for a period of 570 days to document the kinetics of faecal egg output, adults worm population, morphological development, fecundity, and hematological changes including peripheral blood eosinophilia. This study chronicled a life long parasitism of S. venezuelensis in the gerbil host, and showed that S. venezuelensis infection was quite stable throughout the course of infection and the worms maintained their normal development as evidenced by their body dimension. A progressive loss of body condition of the infected gerbils was observed as the level of infection advanced. However, no detectable pathological changes were observed in the gastrointestinal tract. The present findings indicate that an immunocompetent host, such as the Mongolian gerbil, can serve as a life long carrier model of S. venezuelensis if the worms are not expelled within 570 days after infection.